2016
DOI: 10.1371/journal.pone.0153983
|View full text |Cite
|
Sign up to set email alerts
|

MDR-TB Outbreak among HIV-Negative Tunisian Patients followed during 11 Years

Abstract: BackgroundMultidrug-resistant tuberculosis (MDR-TB) outbreaks that evolve, from the outset, in a context strictly negative for HIV infection deserve special consideration since they reflect the true intrinsic epidemic potential of the causative strain. To our knowledge, the long-term evolution of such exceptional outbreaks and the treatment outcomes for the involved patients has never been reported hitherto. Here we provide a thorough description, over an 11-year period, of an MDR-TB outbreak that emerged and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…cgMLST analysis showed that 65.2% of MDR/XDR strains of M. tuberculosis were clustered, reflecting extensive transmission in Tunisia, particularly of a Haarlem clone. This Haarlem clone showed polymorphisms rpoB Ser450Leu, Val534Met, katG Ser315Thr, embB Met306Ile, and gidB Arg47Trp, and in pncA genes previously identified in a Haarlem MDR TB outbreak in the Bizerte region during 2001–2011 ( 13 , 14 ). As indicated by statistical association, we conclude that this cluster is still spreading in the Bizerte area.…”
Section: Discussionmentioning
confidence: 57%
“…cgMLST analysis showed that 65.2% of MDR/XDR strains of M. tuberculosis were clustered, reflecting extensive transmission in Tunisia, particularly of a Haarlem clone. This Haarlem clone showed polymorphisms rpoB Ser450Leu, Val534Met, katG Ser315Thr, embB Met306Ile, and gidB Arg47Trp, and in pncA genes previously identified in a Haarlem MDR TB outbreak in the Bizerte region during 2001–2011 ( 13 , 14 ). As indicated by statistical association, we conclude that this cluster is still spreading in the Bizerte area.…”
Section: Discussionmentioning
confidence: 57%
“…Patients with DM have not been specifically studied, although clinical manifestations among patients with TB and DM indicate that patients with DM might have an important role in TB transmission. Moreover, patients with DM have been described as index and secondary cases in TB outbreaks [ 57 , 58 ]. Usage of molecular epidemiologic techniques has previously allowed us to show that increased risk of TB among patients with DM is due to both reactivation and recently transmitted infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of exogenous reinfection in one-fifth of the cases suggested that exogenous TB reinfection in DM patients might be due to nosocomial TB transmission occurring as a result of DM patients attending clinics where there is a high prevalence of diagnosed and undiagnosed TB, as has been described for HIV infected patients [ 74 ]. Patients with DM have been described as index and secondary cases in TB outbreaks [ 75 , 76 ]. Therefore, there are grounds to hypothesize that patients with DM and TBP may have a greater likelihood of recent transmission than TBP patients without DM.…”
Section: Discussionmentioning
confidence: 99%